2021
DOI: 10.3390/pharmaceutics13070991
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones: Promising Natural Compounds to Fight Inflammation

Abstract: Inflammation is a crucial and complex process that reestablishes the physiological state after a noxious stimulus. In pathological conditions the inflammatory state may persist, leading to chronic inflammation and causing tissue damage. Sesquiterpene lactones (SLs) are composed of a large and diverse group of highly bioactive plant secondary metabolites, characterized by a 15-carbon backbone structure. In recent years, the interest in SLs has risen due to their vast array of biological activities beneficial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 102 publications
(182 reference statements)
0
41
0
Order By: Relevance
“…Bioactive dietary components play a large role in regulating gut health and resistance to enteric pathogen infections. Our recent work with chicory has identified that SL have a clear anthelmintic activity, and it is known that SL (especially those derived from chicory) are anti-inflammatory and antibacterial compounds [32, 33]. Thus, we examined the effects on parasitic infection and gut microbiota in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive dietary components play a large role in regulating gut health and resistance to enteric pathogen infections. Our recent work with chicory has identified that SL have a clear anthelmintic activity, and it is known that SL (especially those derived from chicory) are anti-inflammatory and antibacterial compounds [32, 33]. Thus, we examined the effects on parasitic infection and gut microbiota in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-in ammatory effect of 8deoxylactucin is mediated by two mechanisms: 1) inhibition of NF-kB activity and 2) cyclooxygenase (COX-2) inhibition [26]. In an in vitro study, it has been shown that SLs extracted from chicory root, in a dose-dependent manner downregulated the genes expression of COX-2, inducible nitric oxide synthase (iNOS), TNF-α and IL-1β in LPS-stimulated macrophages [27]. It was observed that lactucin and lactucopicrin, found in CI, exerted an analgesic effect in the tail-ick and hot plate tests in mice and their antinociceptive activity was similar to ibuprofen [17,28].…”
Section: Discussionmentioning
confidence: 99%
“…The α-methylene-γ-lactone moiety of these molecules is a reactive entity, capable of Michael-type addition with biological nucleophiles, in particular with the sulfhydryl groups of proteins [4] (Figure 8). BRT has been shown to bind covalently to a cysteine residue (Cys-151) of Keap1 [85], and helenalin shows a high reactivity toward specific thiolcontaining proteins, such as the p65 subunit of NFκB [10,11].…”
Section: Thiol Reactivitymentioning
confidence: 99%
“…They usually display prominent antioxidant and anti-inflammatory properties. Many natural products in this large family have been considered for the treatment of human diseases, including inflammatory diseases, metabolic syndrome, parasitic diseases and cancers [2][3][4].…”
Section: Introductionmentioning
confidence: 99%